The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1034/j.1399-3046.2001.005004297.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of interleukin‐2 receptor blockade with basiliximab in pediatric renal transplant recipients

Abstract: Rejection remains a major threat in pediatric renal transplantation (Tx), causing graft failure and increased exposure to drugs. The new chimeric antibody, basiliximab, directed against the alpha-chain of the interleukin-2 receptor (IL-2R), has been shown to be effective in preventing rejection episodes in adult renal transplant recipients. In our single-center experience from Essen, Germany, we evaluated prospectively the efficacy and tolerability of basiliximab, in combination with cyclosporin A (CsA) and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 13 publications
(12 reference statements)
2
17
1
Order By: Relevance
“…Most patients were treated according to the local immunosuppressive protocol consisting of basilximab, cyclosporine A, and prednisone as described elsewhere (15).…”
Section: Methodsmentioning
confidence: 99%
“…Most patients were treated according to the local immunosuppressive protocol consisting of basilximab, cyclosporine A, and prednisone as described elsewhere (15).…”
Section: Methodsmentioning
confidence: 99%
“…The large majority of these studies investigated recipients receiving ciclosporin as the calcineurin inhibitor; relatively few studies have investigated the addition of an interleukin-2 receptor to a tacrolimus-based immunosuppressive regimen. In children, the North American Pediatric Renal Trials and Collaborative Studies (NAPRTCS) registry has reported that there is an increase in acute rejection in children who did not receive an interleukin-2 receptor antagonist [3], and a number of other reports have indicated that these agents appear to be safe and efficacious [4][5][6][7].…”
Section: Introductionmentioning
confidence: 97%
“…In pediatric renal transplantation, isolated reports have demonstrated that induction therapy with basiliximab combined with calcineurin inhibitors is safe and efficacious (10)(11)(12)(13). However, so far there have been no randomized, controlled, prospective trials in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%